An Autonomous English Learning Model Performed By Non-English Lecturer - Songkaton, Jihan Fahira; Halimah, Nur (Institut Agama Islam Negeri (IAIN) Manado, 2024)
This research aims to explore the model of autonomous English language learning implemented by a non-English lecturer at IAIN Manado. The research uses a qualitative approach with a case study method and employs three instruments: observation, interviews, and documentation. To conduct, the researchers identify one research subject whose status as the non-English lecturer but teaching English in IAIN Manado. To analyze, the researchers conduct Miles and Huberman’s analysis model through data reduction, data display and data verification. The results indicate that the non-English lecturer adopted a Semi-Autonomous Learning (SAL) model while in high school and a Full Autonomous Learning (FAL) model since becoming a lecturer. Factors influencing the lecturer's autonomous English learning include internal and external factors, such as interest in learning, motivation, and needs. Additionally, the lecturer's self-directed learning activities include attending various webinars, seminars, or international conferences, writing articles in English, utilizing English learning media, reading English textbooks, and familiarizing themselves with English references. The challenges faced in implementing autonomous English learning as a non-English lecturer include limited study time and a less supportive work environment. To address these challenges, the lecturer uses weekend breaks to engage in deeper self-study at home by participating in international classes or webinars. Furthermore, this research highlights the potential model to be effectively adopted, underscores the internal and external factors for learning practices, follow up the following problems to have a good institutional policy. Recommendations could include creating flexible schedules, integrating language learning opportunities into faculty development programs, and fostering a good community to practice and share strategies as well as experiences.Keywords: autonomous learning, non-English lecturer, English language